Toxicity of imidacloprid to the earthworm Eisenia andrei and collembolan Folsomia candida in three contrasting tropical soils - Bandeira F.O.* (2020)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.Purpose: Imidacloprid is a widely used seed dressing insecticide in Brazil. However, the effects of this pesticide on non-target organisms such as soil fauna still present some knowledge gaps in tropical soils. This study aimed to assess the toxicity and risk of imidacloprid to earthworms Eisenia andrei and collembolans Folsomia candida in three contrasting Brazilian tropical soils. Materials and methods: Acute and chronic toxicity assays were performed in the laboratory with both species in a tropical artificial soil (TAS) and in two natural soils (Oxisol and Entisol), at room temperature of 25 °C. The ecological risk was calculated for each species and soil by using the toxicity exposure ratio (TER) and hazard quotient (HQ) approaches. Results and discussion: Acute toxicity for collembolans and earthworms was higher in Entisol (LC50 = 4.68 and 0.55 mg kg−1, respectively) when compared with TAS (LC50 = 10.8 and 9.18 mg kg−1, respectively) and Oxisol (LC50collembolans = 25.1 mg kg−1). Chronic toxicity for collembolans was similar in TAS and Oxisol (EC50 TAS = 0.80 mg kg−1; EC50 OXISOL = 0.83 mg kg−1), whereas higher toxicity was observed in Entisol (EC50 = 0.09 mg kg−1). In chronic assays with earthworms, imidacloprid was also more toxic in Entisol (EC50 = 0.21 mg kg−1) when compared to TAS (EC50 = 1.89 mg kg−1). TER and HQ values indicated a significant risk of exposure of the species to imidacloprid in all soils tested, and the risk in Entisol was at least six times higher than in Oxisol or TAS. Conclusions: The toxicity and risk of imidacloprid varied significantly between tropical soils, being the species exposure to this pesticide particularly hazardous in very sandy natural soils such as Entisol.